A preliminary investigation of the ecology of the Larger Kleinmond River Estuary, Bathurst District - Brown, Alexander Claude, 1931-2005 (Rhodes University, Faculty of Science, Department of Zoology, 1953)
Introduction. On the coast of the Bathurst Division, Eastern Cape Province, some 42 miles south- east of Grahamstown, lie two estuaries opening within a few yards of one another. These are known as the Kleinemonde. This paper embodies the results of an ecological survey of the fauna of the Larger Kleinmond Estuary. The chief concern has been the aquatic fauna but animals living along the banks have also been dealt with as far as possible, as have the birds. This is the second of South Africa's blind estuaries to be studied, the Klein River, Hermanus, having been investigated in 1947-49 by workers from the University of Cape Town. Though common in South Africa, blind estuaries are rare in parts of the world such as Europe, and present an almost entirely new field of research for the ecologist. It is hoped, therefore, that the investigation of the Kleinmond Estuary and a comparison with the results obtained from the Klein River, Hermanus, will add to our knowledge of this subject and be of service to future investigators. The history of the Kleimnond River is worthy of mention, for the lagoon was not always blind and shallow. The early maps of the 1820 settlers show the river as a navigable stream; sailing vessels anchored out at sea and sent lighters up what was then known as the Lydendoch River to collect fresh meat. The area at the mouth of the river was called Port Jessie. In these early days the region abounded with game. Hippo and elephant were common. the former inhabiting deep pools in the upper reaches of the river; pools which have since completely silted up. Constant ploughing of the slopes adjoining the river has caused vast amounts of soil to be washed by rains into the stream, and today what was within living memory a deep, clear stream is a shallow, blind and muddy river, a reflection of man's destructive methods of farming. These changes must have had a far-reaching effect on the fauna of the estuary; an effect about which we can, alas, only speculate. It is perhaps significant that though rich in numbers, the fauna is poor in species, tunicates and echinoderms being apparently entirely absent. The work involved in this survey was undertaken between September 1952 and November 1953, under the direction of Professor J . Omer-Cooper of Rhodes University, frequent and regular visits being made to the estuary. The entire month of February, 1953, was spent on the shore of the lagoon, so that animals could be observed over a continuous period. The starting date of the survey was particularly fortunate, as on September 28th, 1952, the river came down in flood and broke through the sand-bar separating the lagoon from the sea. The work thus began at a definite point in the estuarine cycle, the importance of which it is hoped to show.
Keywords: Kleinemonde River Estuary (South Africa); Estuaries -- South Africa; Estuarine ecology -- South Africa